Hypoxia-adenosinergic regulation of B cell responses - Pruitt, Layne; Abbott, Robert K. (Frontiers in Immunology, 2024)
Hypoxic microenvironments induce widespread metabolic changes that have been shown to be critical in regulating innate and adaptive immune responses. Hypoxia-induced changes include the generation of extracellular adenosine followed by subsequent signaling through adenosine receptors on immune cells. This evolutionarily conserved “hypoxia-adenosinergic” pathway of hypoxia → extracellular adenosine → adenosine receptor signaling has been shown to be critical in limiting and redirecting T cell responses including in tumor microenvironments and the gut mucosa. However, the question of whether hypoxic microenvironments are involved in the development of B cell responses has remained unexplored until recently. The discovery that germinal centers (GC), the anatomic site in which B cells undergo secondary diversification and affinity maturation, develop a hypoxic microenvironment has sparked new interest in how this evolutionarily conserved pathway affects antibody responses. In this review we will summarize what is known about hypoxia-adenosinergic microenvironments in lymphocyte development and ongoing immune responses. Specific focus will be placed on new developments regarding the role of the hypoxia-adenosinergic pathway in regulating GC development and humoral immunity.